Glass ceramic as well as preparation method and application thereof
A microcrystalline glass with Ba2SiO4:Eu2+ and BaSiO3:Eu2+ phases addresses thermal quenching and cost issues in solid-state lighting, providing efficient and stable luminescence for high-power applications.
Patent Information
- Application Number
- CN202411106067.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-13
AI Technical Summary
Existing solid-state lighting technologies face challenges with high heat generation leading to thermal quenching, color drift, and reduced luminous efficiency, particularly in high-power applications, and existing luminescent materials like single crystals and ceramics are costly and difficult to mass-produce.
A microcrystalline glass composed of Ba2SiO4:Eu2+ and BaSiO3:Eu2+ phases, prepared through controlled crystallization of SiO2, BaO, and Eu2O3, offering high luminous efficiency, thermal stability, and low cost, suitable for outdoor displays and high-power lighting.
The microcrystalline glass exhibits excellent thermal stability, high transparency, and luminous efficiency, with quantum efficiency over 88% and minimal luminance loss after immersion, making it suitable for high-power lighting and displays.
Smart Images

Figure CN119118514A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid luminescent materials, and in particular relates to a microcrystalline glass and a preparation method and application thereof. Background Art
[0002] At present, solid-state lighting is widely used for its comprehensive advantages such as energy saving, environmental protection, compactness, and long life. Solid-state lighting refers to the technology of lighting using solid-state electronic components as the excitation source, represented by light-emitting diodes (LEDs) and laser diodes (LDs). Due to the limitations of the stimulated characteristics of semiconductors and lasers, it is impossible to obtain a continuous white light spectrum by relying solely on solid-state electronic components. In order to obtain a continuous white light spectrum, it is usually necessary to couple the luminescent material with the LED / LD chip to obtain a white light lighting device. For example, the white light LED (WLED) and LD lighting devices on the market are composed of a blue LED / LD chip and a yellow YAG:Ce 3+ Phosphor composition.
[0003] For high-power lighting, the heat generated by energy loss (such as photoelectric energy conversion, Stokes shift of luminescent materials) will increase dramatically. It is reported that the cumulative heat release of high-power LED chips during operation can even exceed 200°C, and under the irradiation of 10W blue light LD, the internal temperature of the LD device can reach 260°C within 10 minutes. Under such long-term high-temperature irradiation, phosphors will face problems such as thermal quenching and decreased luminous efficiency, and will inevitably bring serious problems such as color drift and reduced luminous efficiency. In addition, under the irradiation of high-power chips, it is inevitable to accelerate the aging and yellowing of organic adhesives with poor heat resistance such as resins or silicone resins, and even ablation. Therefore, the heat dissipation problem has become one of the main bottlenecks restricting the development of high-power solid-state lighting. On the basis of existing LED / LD chip technology, exploring luminescent materials with high luminous efficiency and excellent thermal stability has posed a severe challenge.
[0004] For this reason, more and more scientists have begun to focus on solid luminescent materials with excellent optical properties. Solid luminescent materials mainly include: single crystals, ceramics and glass. Single crystals and ceramics have high manufacturing costs and cannot be mass-produced, which greatly limits their wide application in the market, while glass has the disadvantage of low luminescence efficiency due to its amorphous structure.
[0005] Therefore, there is an urgent need to provide a new solid luminescent material. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a microcrystalline glass and a preparation method and application thereof. The microcrystalline glass of the present invention has excellent stability and luminous performance, and can be widely used in the display or lighting field, and is particularly suitable for outdoor display and high-power lighting fields.
[0007] The microcrystalline glass of the present invention is a microcrystalline glass (glass ceramic) containing a large amount of microcrystalline phase (belonging to phosphor crystal) and glass phase, which can be obtained by controlling the crystallization of specific component raw materials during heating. 2+ ) doped microcrystalline glass combines the advantages of phosphor crystals and glass, and has the advantages of high luminous efficiency, excellent thermal stability and high transparency, and has hard, dense and uniform texture, flexible control of components, corrosion resistance, easy processing and molding, low cost and large-scale production. The microcrystalline glass of the present invention also has a viscous network structure that makes the microcrystals dispersed evenly. Therefore, the microcrystalline glass of the present invention has the above advantages at the same time and can be applied to outdoor display and high-power lighting fields.
[0008] A first aspect of the present invention provides a glass-ceramic.
[0009] Specifically, a microcrystalline glass includes Ba2SiO4:Eu 2+ Single crystal phase, or Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ At least one of the twin crystal phases.
[0010] Preferably, the Ba2SiO4:Eu 2+ The single crystal phase has an elongated strip-like morphology.
[0011] Preferably, the Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ The twin crystal phase has an elongated strip-like morphology.
[0012] Preferably, the Ba2SiO4:Eu 2+ Single crystal phase, Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ The grain length of the twin crystal phase is 50-550 μm, more preferably 100-500 μm.
[0013] Preferably, the glass-ceramics can emit a strong broadband spectrum in the 420 to 650 nm band under 365 nm light excitation, and further the main emission peak is located at 508 nm.
[0014] Preferably, the quantum efficiency of the glass-ceramics is not less than 88%, for example, 88-92%.
[0015] Preferably, after the glass-ceramics is immersed in water for 60 days, the luminous intensity decreases by no more than 3%, for example, the luminous intensity decreases by 1-3%.
[0016] A second aspect of the present invention provides a method for preparing glass-ceramics.
[0017] Specifically, a method for preparing glass-ceramics includes the following steps:
[0018] Weighing SiO2, BaO, and Eu2O3 raw materials, then mixing them, heating and melting them in a reducing atmosphere, and then cooling them to obtain the microcrystalline glass;
[0019] In the raw material, the molar percentage of SiO2 is 40-60%, the molar percentage of BaO is 40-60%, and the molar percentage of BaO is greater than the molar percentage of SiO2;
[0020] The heating and melting temperature exceeds 1500°C.
[0021] Preferably, in the raw material, the molar percentage of Eu2O3 is 0.01-2%, and more preferably 0.1-0.2%.
[0022] Preferably, in the raw material, the molar percentage of SiO2 is 40-60%, the molar percentage of BaO is 40-60%, the molar percentage of Eu2O3 is 0.01-2%, and the molar percentage of BaO is greater than the molar percentage of SiO2.
[0023] Further preferably, in the raw materials, the molar percentage of SiO2 is 45%, the molar percentage of BaO is 54.8%, and the molar percentage of Eu2O3 is 0.2%.
[0024] Preferably, the heating and melting temperature is 1580-1650°C, more preferably 1580-1600°C.
[0025] Preferably, the heating and melting temperature is maintained at 1580-1650° C. for 0.8-6 hours, more preferably for 1-6 hours.
[0026] Preferably, the reducing atmosphere is selected from at least one of H2, CO or carbon powder.
[0027] Preferably, the mixing process is carried out by grinding, for example, grinding for 20-30 minutes.
[0028] Preferably, the cooling is natural cooling to room temperature, for example, cooling to room temperature in a muffle furnace.
[0029] Preferably, the cooling time is 8-10 hours.
[0030] A third aspect of the present invention provides an application of glass-ceramics.
[0031] A display or lighting device comprises the above-mentioned microcrystalline glass.
[0032] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0033] (1) The present invention adopts specific preparation conditions (raw material ratio and heating melting temperature) to prepare transparent fluorescent Ba2SiO4:Eu with long crystal morphology. 2+ Single crystal phase or Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ The double-crystal phase microcrystalline glass has a hard, dense and uniform texture, stable physical and chemical properties (after immersion in water for 60 days, the luminous intensity drops by no more than 3%), and can emit strong green light under ultraviolet light excitation (quantum efficiency is not less than 88%).
[0034] (2) The present invention economically and affordably uses SiO2, BaO and Eu2O3 as raw materials to prepare glass-ceramics, and the preparation cost is low.
[0035] (3) The present invention prepares a transparent fluorescent microcrystalline glass with adjustable structure and long strip crystal morphology. The crystal phase in the microcrystalline glass can be selected from Ba2SiO4:Eu 2+ Single crystal phase modulation into Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ Twin crystal phase.
[0036] (4) The microcrystalline glass of the present invention is prepared in a one-step process, which has simple process, low cost, non-toxicity and pollution-free. The microcrystalline glass material has excellent luminescence performance and can be developed as a green fluorescent solid luminescent material for application in laser lighting. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is the XRD pattern of the glass-ceramics prepared in Example 1 of the present invention;
[0038] Figure 2 is a digital photo of the glass-ceramics prepared in Example 1 of the present invention;
[0039] Figure 3 is a morphology image of the glass-ceramics prepared in Example 1 of the present invention taken under an optical microscope;
[0040] Figure 4 is a morphology image taken by a scanning electron microscope (SEM) of the glass-ceramics prepared in Example 1 of the present invention;
[0041] Figure 5 is a normalized excitation and emission spectrum diagram of the glass-ceramics prepared in Example 1 of the present invention;
[0042] Figure 6 It is a comparison diagram of spectral intensities of the glass-ceramics prepared in Example 1 of the present invention in water for 0 day and 60 days;
[0043] Figure 7 It is the normalized excitation and emission spectrogram of the glass-ceramics prepared in Example 2 of the present invention;
[0044] Figure 8 It is the normalized excitation and emission spectrogram of the glass-ceramics prepared in Example 3 of the present invention;
[0045] Fig. 9 It is the normalized excitation and emission spectrogram of the glass-ceramics prepared in Example 4 of the present invention;
[0046] Fig.10 It is the XRD diagram of the amorphous glass prepared in Comparative Example 1 of the present invention. Detailed implementation manners
[0047] To make those skilled in the art more clearly understand the technical solutions described in the present invention, the following examples are listed for illustration. It should be noted that the following examples do not limit the scope of protection required by the present invention.
[0048] In the following examples, the raw materials, reagents or devices used, unless otherwise specified, can be obtained from conventional commercial channels or can be obtained by existing known methods.
[0049] Figure 1 In [description], "Intensity" represents intensity, 2θ represents diffraction angle, "degree" represents degree, "PDF#70-2113" represents the standard card of Ba2SiO4, and "PDF#70-2112" represents the standard card of BaSiO3.
[0050] Figures 5 to 9 In [description], "Intensity" represents intensity and "Wavelength" represents wavelength.
[0051] Figure 6 In [description], "day" represents day.
[0052] Fig.10 In [description], "Intensity" represents intensity, 2θ represents diffraction angle, and "degree" represents degree.
[0053] Example 1
[0054] A glass-ceramic comprising Ba2SiO4:Eu 2+ Single crystal phase.
[0055] A method for preparing a glass-ceramic, comprising the following steps:
[0056] S1. Weigh the required raw materials SiO2, BaO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.8 mol% BaO, and 0.2 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;
[0057] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature in the muffle furnace over 9 hours to obtain a block containing Ba2SiO4:Eu 2+ Single crystal phase glass-ceramics.
[0058] Figure 1 is the XRD pattern of the glass-ceramics prepared in Example 1 of the present invention; Figure 2 is a digital photo of the glass-ceramics prepared in Example 1 of the present invention; Figure 3 is a morphology image of the glass-ceramics prepared in Example 1 of the present invention taken under an optical microscope;
[0059] Figure 4 is a morphology image taken by a scanning electron microscope (SEM) of the glass-ceramics prepared in Example 1 of the present invention; Figure 5 is a normalized excitation and emission spectrum diagram of the glass-ceramics prepared in Example 1 of the present invention; Figure 6 is a comparison chart of the spectral intensity of the glass-ceramics prepared in Example 1 of the present invention in water at 0 day and 60 days;
[0060] from Figure 1 It can be seen from the X-ray diffraction peaks that Ba2SiO4:Eu has been precipitated in the prepared microcrystalline glass. 2+ Single crystal phase.
[0061] The prepared glass-ceramics still has a certain degree of transparency when the thickness is 2 mm, and there are long strips of crystals visible to the naked eye embedded in the glass on the surface of the glass-ceramics (see Figure 2 ).
[0062] Under an optical microscope, it was clearly observed that a glass-ceramic with a long strip-shaped crystal morphology was successfully prepared (see Figure 3 ).
[0063] Further, under the scanning electron microscope (SEM), it was observed that the crystals were clearly strip-shaped, and the length of the crystals was about 100-500 μm (see Figure 4 ).
[0064] Under the excitation of 365nm wavelength violet light, the glass-ceramics prepared in this example exhibits bright green luminescence. The normalized excitation and emission spectra at room temperature are measured using an Edinburgh FS980 fluorescence spectrometer. Figure 5 As shown; Eu can be observed from the emission spectrum 2+ 4f of ions 6 5d 1 -4f 7 The transition is a typical broad-peak emission with a central wavelength of 508nm. The excitation spectrum covers a wide band of 250-480nm. What is important is that the excitation peak is at 365nm, which can effectively match the 365nm ultraviolet chip widely used on the market, which is conducive to market application.
[0065] from Figure 6 It can be seen that the microcrystalline glass prepared in this embodiment has excellent stability. After being immersed in water for 60 days (60 days) at room temperature, the luminescence intensity only decreases by 3% compared with not immersed in water (i.e. 0 day). In addition, the microcrystalline glass prepared in this embodiment has excellent luminescence performance, and the quantum efficiency reaches 90%.
[0066] Example 2
[0067] A glass-ceramic comprising Ba2SiO4:Eu 2+ Single crystal phase.
[0068] A method for preparing glass-ceramics comprises the following steps:
[0069] S1. Weigh the required raw materials SiO2, BaO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.95 mol% BaO, and 0.05 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;
[0070] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature in the muffle furnace over 9 hours to obtain a block containing Ba2SiO4:Eu 2+ Single crystal phase glass-ceramics.
[0071] Figure 7 It is a normalized excitation and emission spectrum diagram of the microcrystalline glass prepared in Example 2 of the present invention.
[0072] from Figure 1 It can be seen from the X-ray diffraction peaks that Ba2SiO4:Eu 2+ Single crystal phase.
[0073] Under the excitation of 365nm wavelength violet light, the microcrystalline glass prepared in this embodiment exhibits bright green luminescence. The normalized excitation and emission spectra at room temperature are measured using an Edinburgh FS980 fluorescence spectrometer. Figure 7As shown; the emission spectrum can be observed Eu 2+ 4f of ions 6 5d 1 -4f 7 The transition is a typical broad-peak emission with a central wavelength of 508 nm. The excitation spectrum covers a wide band of 250-480 nm, and the excitation peak is at 365 nm.
[0074] Example 3
[0075] A glass-ceramic comprising Ba2SiO4:Eu 2+ Single crystal phase.
[0076] A method for preparing glass-ceramics comprises the following steps:
[0077] S1. Weigh the required raw materials SiO2, BaO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.5 mol% BaO, and 0.5 mol% Eu2O3, mix and grind for 30 min, and place the mixed and ground raw materials in a crucible;
[0078] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature in the muffle furnace over 9 hours to obtain a block containing Ba2SiO4:Eu 2+ Single crystal phase glass-ceramics.
[0079] Figure 8 It is the normalized excitation and emission spectra of the microcrystalline glass prepared in Example 3 of the present invention.
[0080] from Figure 1 It can be seen from the X-ray diffraction peaks that Ba2SiO4:Eu 2+ Single crystal phase.
[0081] Under the excitation of 365nm wavelength violet light, the microcrystalline glass prepared in this embodiment exhibits bright green luminescence. The normalized excitation and emission spectra at room temperature are measured using an Edinburgh FS980 fluorescence spectrometer. Figure 8 As shown; the emission spectrum can be observed Eu 2+ 4f of ions 6 5d 1 -4f 7 The transition is a typical broad-peak emission with a central wavelength of 508 nm. The excitation spectrum covers a wide band of 250-480 nm, and the excitation peak is at 365 nm.
[0082] Example 4
[0083] A glass-ceramic comprising Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ Twin crystal phase.
[0084] A method for preparing glass-ceramics comprises the following steps:
[0085] S1. Weigh the required raw materials SiO2, BaO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54 mol% BaO, and 1 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;
[0086] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature over 8 hours in the muffle furnace to obtain a block containing Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ Glass-ceramics with twin crystal phases.
[0087] Fig. 9 It is the normalized excitation and emission spectra of the microcrystalline glass prepared in Example 4 of the present invention.
[0088] from Figure 1 It can be seen from the X-ray diffraction peaks that Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ Twin crystal phase.
[0089] Under the excitation of 365nm wavelength violet light, the microcrystalline glass prepared in this embodiment exhibits bright green luminescence. The normalized excitation and emission spectra at room temperature are measured using an Edinburgh FS980 fluorescence spectrometer. Fig. 9 As shown; the emission spectrum can be observed Eu 2+ 4f of ions 6 5d 1 -4f 7 The transition is a typical broad-peak emission with a central wavelength of 508 nm. The excitation spectrum covers a wide band of 250-480 nm, and the excitation peak is at 365 nm.
[0090] Comparative Example 1
[0091] A method for preparing glass comprises the following steps:
[0092] S1. Weigh the required raw materials SiO2, BaO, and Eu2O3 according to the molar fractions of 45 mol% SiO2, 54.8 mol% BaO, and 0.2 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;
[0093] S2. Place the crucible containing the raw materials in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, keep it warm in a muffle furnace at 1400° C. for 1 hour, and then slowly cool it from 1400° C. to room temperature over 9 hours in the muffle furnace to obtain a product.
[0094] Fig.10 It is the XRD diagram of the amorphous glass prepared in Comparative Example 1 of the present invention.
[0095] In this comparative example, due to the low melting temperature, bulk microcrystalline glass cannot be obtained, and only bulk amorphous glass can be obtained (see Fig.10 ).
[0096] Comparative Example 2
[0097] A method for preparing glass-ceramics comprises the following steps:
[0098] S1. Weigh the required raw materials SiO2, BaO, and Eu2O3 according to the molar fractions of 50 mol% SiO2, 49.5 mol% BaO, and 0.5 mol% Eu2O3, mix and grind for 30 min, and place the mixed and ground raw materials in a crucible;
[0099] S2. Place the crucible with the raw material in a large crucible with a lid covered with activated carbon powder as a reducing atmosphere, and heat it in a muffle furnace at 1600°C for 1 hour to melt it. After melting, slowly cool it from 1600°C to room temperature over 9 hours in the muffle furnace to obtain a block containing BaSiO3:Eu 2+ Single crystal phase glass-ceramics.
[0100] Comparative Example 3
[0101] A method for preparing glass comprises the following steps:
[0102] S1. Weigh the required raw materials SiO2, BaO, and Eu2O3 according to the molar fractions of 70 mol% SiO2, 29.5 mol% BaO, and 0.5 mol% Eu2O3, mix and grind for 30 minutes, and place the mixed and ground raw materials in a crucible;
[0103] S2. Place the crucible with the raw materials in a large covered crucible covered with activated carbon powder as a reducing atmosphere, keep it warm in a muffle furnace at 1600°C for 1 hour to melt it, and then slowly cool it from 1600°C to room temperature in the muffle furnace over 9 hours to obtain a block of amorphous glass.
[0104] A display device comprises the microcrystalline glass of embodiment 1.
[0105] A lighting device comprises the microcrystalline glass of embodiment 2.
[0106] On the basis of the above embodiments and within the scope of protection requested by the present invention, changes to the technical solutions of the present invention, such as changes in the dosage of the raw materials of the present invention, temperature and time, etc., which do not require creative labor, all fall within the scope of protection of the present invention.
Claims
1. A glass-ceramic, characterized in that: Including Ba2SiO4:Eu 2+ Single crystal phase, or Ba2SiO4:Eu 2+ and BaSiO3:Eu 2 + At least one of the twin crystal phases.
2. The glass-ceramic according to claim 1, characterized in that: The Ba2SiO4:Eu 2+ The single crystal phase has a long strip morphology; and / or, the Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ The twin crystal phase has an elongated strip-like morphology.
3. The glass-ceramic according to claim 1, characterized in that: The Ba2SiO4:Eu 2+ Single crystal phase, Ba2SiO4:Eu 2+ and BaSiO3:Eu 2+ The grain length of the twin crystal phase is 50-550 μm.
4. The glass-ceramic according to claim 1, characterized in that: The microcrystalline glass can emit a broadband spectrum in the 420 to 650 nm band under 365 nm light excitation.
5. The glass-ceramic according to claim 1, characterized in that: The quantum efficiency of the microcrystalline glass is not less than 88%.
6. The glass-ceramic according to claim 1, characterized in that: After the microcrystalline glass is immersed in water for 60 days, the luminous intensity decreases by no more than 3%.
7. The method for preparing glass-ceramics according to any one of claims 1 to 6, characterized in that: The following steps are involved: Weighing SiO2, BaO, and Eu2O3 raw materials, then mixing them, heating and melting them in a reducing atmosphere, and then cooling them to obtain the microcrystalline glass; In the raw material, the molar percentage of SiO2 is 40-60%, the molar percentage of BaO is 40-60%, and the molar percentage of BaO is greater than the molar percentage of SiO2; The heating and melting temperature exceeds 1500°C.
8. The preparation method according to claim 7, characterized in that: In the raw material, the molar percentage of Eu2O3 is 0.01-2%.
9. The preparation method according to claim 7, characterized in that: The heating and melting temperature is 1580-1650°C, and the heating and melting temperature of 1580-1650°C is kept for 0.8-6 hours; and / or, the reducing atmosphere is selected from at least one of H2, CO or carbon powder.
10. A display or lighting device, characterized in that: The present invention comprises the glass-ceramics as described in any one of claims 1 to 6.
Citation Information
Patent Citations
Microcrystalline glass for warm white LED and preparation method thereof
CN106517797A
Fluorescent glass ceramic material, manufacture method thereof and illuminating device thereof
CN108558213A
Purple light excitation glass ceramic for LED (light-emitting diode) illumination and preparation method of purple light excitation glass ceramic
CN115716707A
